Cenozoic Exhumation of the Ailaoshan‐Red River Shear Zone: New Insights From Low‐Temperature Thermochronology. Issue 9 (24th September 2020) - Wang, Yang; Wang, Yuejun; Schoenbohm, Lindsay M.; Zhang, Peizhen; Zhang, Bo; Sobel, Edward R.; Zhou, Renjie; Shi, Xuhua; Zhang, Jinjiang; Stockli, Daniel F.; Guo, Xiaofei
Abstract: Continental‐scale shear zones play an important role in accommodating block extrusion and rotation as shown by deformation on the Ailaoshan‐Red River shear zone (ASRRSZ) in the SE Tibetan Plateau. This study presents 13 apatite (U‐Th)/He, 11 zircon (U‐Th)/He, and three apatite fission track dates, together with thermal modeling in the Ailaoshan and Xuelongshan segments (ALSZ and XLSZ) of the shear zone to investigate its Cenozoic exhumation history and mechanism, which are critical for understanding its tectonic and landscape evolution. Our results, combined with published chronologic data, reveal that shear zone rocks along the ALSZ experienced prominent and rapid cooling from high temperature (>500°C) to 120–60°C at a rate of 75–100°C/Myr during 29–17 Ma with northwestward younging onset. A second, lower magnitude accelerated cooling occurred at 14–10 Ma along the ALSZ at a rate of 20–30°C/Myr, with a later initiation on the XLSZ at ~5 Ma and continuing to present with a cooling rate of ~20°C/Myr. Thermal modeling reveals a single rapid cooling phase with a rate of 17–14°C/Myr in the Eocene to early Oligocene for samples outside the shear zones. These three fast cooling episodes are directly related to deformation stages including crustal shortening across the SE plateau, sinistral ductile shearing along the ASRRSZ, and dextral faulting with a dip‐slip component on the Red River and Weixi‐Qiaohou faults along the shear zone flanks. Furthermore, the northward migration of kinematic reversal and associated cooling along strike since the mid‐late Miocene likely reflects the northward advance of the eastern Himalayan syntaxis. Key Points: Two‐stage thermal histories are identified along the ASRRSZ with prominent cooling during sinistral ductile shearing A lower‐magnitude cooling occurred at 14–10 Ma along the ALSZ, with a later onset along the XLSZ, possibly caused by kinematic reversal NW migration of deformation and cooling along the ASRRSZ since the mid‐late Miocene signifies the impact of the northward advancing EHS